Analysis of Transjakarta Bus Fare Adjustment Based on the Ability to Pay (ATP) Method - Gema Krisni Indra Perdana; Dianovita; Octo Alexandro; Gagar Asmara Sofa; Midun Imbas; Saras Fauzia Dienanda (The Journal of Indonesia Sustainable Development Planning, 2026)
TransJakarta's (TJ) fixed fare policy of Rp 3,500, supported by subsidies from the Jakarta Provincial Government (PSO), has kept public transportation fares in Jakarta affordable for the public. However, this policy has also gradually worsened the finances of the Jakarta’s Provincial Government and TJ's own going concern. This study analyzes various fare schemes by comparing users' Ability to Pay (ATP), user travel behavior by survey, and ticket revenue implications to encourage the formulation of new regulations by the Governor of DKI Jakarta on sustainable fares. This analysis uses primary data from the 2023 TransJakarta User Mobility Survey, supplemented by data from the 2021–2022 National Socioeconomic Survey (SUSENAS) and origin-destination (OD) analysis based on Geographic Information Systems (GIS). The methodology used in this study is the Travel Cost Method calculation, which calculates user ATP with the assumption that 10% of household income is spent on transportation. The average travel distance per trip per day is 11.7 km, resulting in an ATP value of Rp 1,237/km. Based on the analysis, the most balanced outcome of the tested scenarios was found to be a tiered fare system based on distance, with a fare of Rp 4,000 for the first 10 km, Rp 416 for each additional kilometer, and a maximum of Rp 14,477. This system increases ticket revenue while maintaining fair and reasonable prices. The study emphasizes the importance of gradual adoption and ongoing monitoring to ensure effective and equitable fare reform.